Proses performance monitoring in pewter manufacturing - Musa, Hamidon; Thean, Chan Tan (Faculty of Mechanical Engineering, 1998)
This paper reports a study on the casting parameters of pewter based on the Taguchi approach. The quality attributes investigated are shrinkage, hardness and microstructure. The paper also reports a study on minimum section thickness producable by gravitycasting and centrifugal casting of pewter components. Additionally, the paper presents results of a study on finish turning of pewter